PERANCANGAN REPOSITORI SERVER PADA STMIK KRISTEN NEUMANN INDONESIA - Yudea lucky putra bukit (UPPM, 2018)
The server repository is a container that can help file sharing activities for every user of the local area network network at STMIK Kristen Neumann Indonesia. In this study the repository was built using php and sql programming languages as a place to store files or data uploaded by the client. Data or files uploaded can be in the form of doc, pdf and even files related to entertainment such as mp3 and others. Every client that uses this server must first be registered as a client in the database.